How the Bible came to be (Muskegon, MI Gospel Films)
"A carefully documented presentation of the originsa of Scripture beautifully photographed in the Holy Land". Contents : v.1 The Old Testament; and v. 2 The New Testament
Keywords: Bible -- introductions